Um pé na terra outro no tribunal : um estudo sobre a proposta de assessoria jurídica popular do Coletivo Margarida Alves - Zanotelli, Ana Gabriela Camatta (2018)
The present study aims to analyze and characterize the public interest lawyering, in view of the growing use of the judicial arena by social movements in the context of political struggles. Through a case study, the Coletivo de Assessoria Jurídica Popular Margarida Alves (a collective of lawyers that offer judicial work for marginalized groups), located in the city of Belo Horizonte, Brazil, we seek to understand how this activity is internally organized and projected in a scenario of confrontation. Via the contentious politics theory and the legal mobilization theory, we analyze the collective of lawyers from its repertoire of action, constituted by plural performances, both political and juridical. It consists on a qualitative research that seeks to understand how the collective constitutes itself as an actor in a context of confrontation, through lawyer’s personal and collective perceptions about the Law and the Justice System, and the relationships they establish with other actors, both allies and opponents. In view of the specificities of the public interest lawyering, characterized by the valorization of affectivity, horizontality and solidarity in the relation to those assisted, there is a process of displacement between the institutional and non-institutional levels. Their practices combine characteristics of both Latin American public interest lawyering, focused on a subversive, critical and transformative use of the Law in the quest for social emancipation, as well as of the pragmatic and strategic North American cause lawyering, which uses available legal instruments in judicial confrontations for rights.